Implementation of the two stay two stray learning model with a realistic mathematics education approach to mathematical understanding ability - Yanti, Rohmah; Umbara, Uba; Sunzuma, Gladys (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2025)
This study aims to determine the effectiveness of the Two Stay Two Stray (TS-TS) learning model combined with the Realistic Mathematics Education (RME) approach in improving students’ mathematical understanding. The research was conducted at SMPN 1 Sindangagung with eighth-grade students as subjects during the 2023/2024 academic year. Class VIII C was assigned as the experimental group and Class VIII D as the control group was selected using purposive sampling. This study used a quasi-experimental design with a non-equivalent pretest-posttest control group format. The instruments used included an essay test to measure mathematical understanding and teacher interview guidelines during the pre-research phase. Data analysis was carried out using normality and homogeneity tests, N-Gain calculations, and the Mann-Whitney U test. The results indicate a statistically significant difference in improvement between the two classes. Practically, the implementation of the TS-TS model based on RME increased student engagement and conceptual understanding, making it a viable alternative for designing active, collaborative, and meaningful mathematics learning.